Indian arrivals, 1870-1915 : networks of British empire - Boehmer, Elleke (O.U.P, 2015)
This title explores the rich and complicated landscape of intercultural contact between Indians and Britons on British soil at the height of empire, as reflected in a range of literary writing, including poetry and travel writing. The book's four decade-based case studies, leading from 1870 and the opening of the Suez Canal to the first years of the Great War, investigate from several different textual and cultural angles the central place of India in the British metropolitan imagination at this relatively early stage for Indian migration and intercultural exchange.